The Use Of Mufradāt Alfāẓ Al-Qur´an In The Translation Of Islamic Terminologies In Malaysian Sign Language Structure - Siti Ramna Binti Khamaruddin
To understand religion terminologies is very important before learning religion more deeply. This understanding is also deserved by the deaf Muslim. However, the sign language books that are used as the main reference in deaf communication does not have clear description. These books only have terms, shape of sign language, how to sign that term and example sentences. This will cause the deaf only know the term without proper understanding. Hence, this research is conducted to translate the meaning of Islamic terminologies in Malaysian Sign Language Book volume 1 and 2 based on the book Mufradāt Alfāẓ al-Qur´ān by Rāghib al-Aṣfahānī in Malaysian Sign Language structure. The book of Mufradāt Alfāẓ al-Qur´ān was chosen because it have in-depth explanation of the Islamic terms in the Qurʾān and easy to understand. This research is also supported by other secondary data. For data analysis, the main method applied is the content analysis method by using intersemiotic approaches, relevance theory and grammar of Malaysian Sign Language to translate Islamic terminologies in Malaysian Sign Language books volume 1 and 2 based on Mufradāt Alfāẓ al-Qur´ān. It is hoped that this study can contribute to the field of translation, especially in translating Islamic terminology to the Structure of Malaysian Sign Language in line with Quranic sources. Meanwhile, in terms of Islamic education can help deaf people to understand the meaning of Islamic terminology according to Quranic sources and at the same time help the Ministry of Education Malaysia (MOE) plan Islamic Education curriculum in preparing Islamic terminology that meets Quranic sources and in line with Malaysian Sign Language structure